2019
DOI: 10.1038/s41598-018-36452-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extracellular vesicles and characterization of miRNA expression profiles in human blastocoel fluid

Abstract: In this study, for the first time, we demonstrated the presence of microRNAs and extracellular vesicles in human blastocoel fluid. The bioinformatic and comparative analyses identified the biological function of blastocoel fluid microRNAs and suggested a potential role inside the human blastocyst. We found 89 microRNAs, expressed at different levels, able to regulate critical signaling pathways controlling embryo development, such as pluripotency, cell reprogramming, epigenetic modifications, intercellular com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 48 publications
6
109
0
Order By: Relevance
“…In line with results demonstrating the sponge activity of circRNAs towards miRNAs [240], circNAPEPLDiso1 has been suggested to physically interact with five miRNAs whose targets are potentially involved in several molecular mechanisms regulating the first stages of embryo development, most of them are known to be expressed in human oocytes, blastocysts and blastocoel fluid [284][285][286].…”
Section: Sperm-derived Circrnas: Potential Modulators Of Sperm Qualitsupporting
confidence: 56%
“…In line with results demonstrating the sponge activity of circRNAs towards miRNAs [240], circNAPEPLDiso1 has been suggested to physically interact with five miRNAs whose targets are potentially involved in several molecular mechanisms regulating the first stages of embryo development, most of them are known to be expressed in human oocytes, blastocysts and blastocoel fluid [284][285][286].…”
Section: Sperm-derived Circrnas: Potential Modulators Of Sperm Qualitsupporting
confidence: 56%
“…Conversely, overexpression of the miR-183/96/182 cluster resulted in a decreased production of nitrite and ROS by macrophage (Muraleedharan et al, 2019) and a neuroprotective role in the brain, by positively regulating glutathione (GSH) levels, a major tissue antioxidant (Kinoshita et al, 2014). Collectively, these studies support the possibility that miR-96 can be decreased in hyperoxic/ oxidative stress conditions; this does not exclude other mechanisms such as extracellular vesicles (Liu and Lu, 2015;Battaglia et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, the two latter epigenetic events are now been recognized as key mechanisms of neoplastic transformation and a plethora of diseases (12,87,150). In this context, recent studies have identified different miRNAs, a class of non-coding RNA of 20-22 nucleotides, associated with the development and progression of different tumors (151)(152)(153)(154)(155)(156)(157).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%